Theoretical estimate of relative depth-doses for the asymmetric and spherical 106Ru/106Rh COC-type plaque used in radiotherapy - Eduardo De Paiva (Brazilian Journal of Radiation Sciences, 2020)
In this work we present results of relative dose rate along central and lateral axis of the 106Ru/106Rh COC model plaque used for the treatment of tumors close to the optical nerve. The calculations were based on the beta-point dose function and are compared with an available data obtained by means of Monte Carlo simulations. Even with the limitations of the method, it was capable to reproduce the general trend of the dose rates around this kind of plaque and a maximum difference of -18% with MC was obtained. Despite the limitations of the method, the results may be used as a guide to future experimental and theoretical studies on this applicator, since there is a lack of available data in literature.